ANALISIS KOLABORASI STAKEHOLDER DALAM PENANGANAN KEKERASAN SEKSUAL DI KOTA SEMARANG - Iqbal Brillianto, Handriyo; Suwitri, Sri; Afrizal, Teuku (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Stakeholder collaboration involves participation, communication, cooperation, and commitment between parties with influence or interest in a program. This study aims to analyze the collaboration among stakeholder in handling sexual violence in the city of Semarang. A qualitative descriptive approach was used with a case study method to describe how stakeholder such as the Women's Empowerment and Child Protection Agency (DP3A), the Regional Technical Implementation Unit for Women's and Children's Protection (UPTD PPA), the Semarang Police, Legal Aid Institutes (LBH), and other related institutions interact and cooperate in handling cases of sexual violence. Data were collected through in-depth interviews, observations, and document analysis, then analyzed using triangulation techniques to ensure the validity of the research findings. The results showed that the collaboration among stakeholder in Semarang has shown some progress in raising public awareness and implementing several outreach programs. However, challenges include a lack of transparency, minimal routine evaluations, and obstacles in cross-agency coordination. Recommendations include increasing transparency and inclusiveness through formal Memorandums of Understanding (MoU), strengthening facilitative leadership through education and training, and optimizing collaborative processes through the development of face-to-face dialogue. Additionally, the utilization of existing resources and capacities, the implementation of specific programs, and continuous monitoring and evaluation are proposed to enhance the effectiveness of collaboration. This study is expected to contribute to efforts to improve stakeholder collaboration in handling sexual violence and serve as a reference for policymakers in formulating more effective strategies in the future.